Tropical monodominant forest resilience to climate change in Central Africa: A Gilbertiodendron dewevrei forest pollen record over the past 2,700 years - Tovar, Carolina; Harris, David J.; Breman, Elinor; Brncic, Terry; Willis, Kathy J. (Journal of vegetation science, 2019)
Question The existence of monodominant forest in highly diverse tropical rainforest has been the subject of much debate. One hypothesis suggests that the combination of advantageous traits and long periods of low disturbance is key for this forest's persistence. Here we ask whether there is evidence for the long‐term presence of monodominant Gilbertiodendron forest in the absence of fire and climate change. Location Republic of Congo. Methods We extracted fossil pollen and macro‐charcoal from a sediment sequence collected in present‐day monodominant Gilbertiodendron forest stand that spans the last 2,700 years. Climatic changes were inferred using other published palaeoecological records from Central Africa. We also looked at Gilbertiodendron dewevrei's present‐day ecological tolerances. Results Gilbertiodendron pollen was found in every sample covering the last 2,700 years in similar percentages to present‐day soil surface samples. In addition, no statistically significant change in pollen composition was found during this time despite vegetation changes being documented in nearby mixed and swamp forest cores over the same time period. No evidence of fire was found for a period of 2,400 years. Only minimal burning occurred over the last 300 years in this monodominant stand. The analysis of ecological tolerances shows G. dewevrei has a broad niche for precipitation (1,300–2,460 mm). Conclusions Our pollen record is the first to describe the long‐term ecological history of an African monodominant forest. Our results show this monodominant stand existed over the past 2,700 years mostly in the absence of fire, providing support for the low disturbance hypothesis as an explanation for monodominance persistence. However, we show that the monodominant forest was continuous, at this site, despite climatic fluctuations in the immediate region. This combined with the broad tolerance of water requirements of the species suggests a potential resilience to future climate variability. However, additional pollen records from a wider area are needed to confirm this. The existence of monodominant forest in highly diverse tropical rainforest has been the subject of much debate. Here, we unveil for the first time the long‐term ecological history of a monodominant Gilbertiodendron forest in Central Africa. We show this monodominant stand existed over the past 2,700 years despite evidence for climatic fluctuations. We discuss potential resilience to future climate variability.